A patient with two retroperitoneal liposarcomas - KOBAYASHI, Mitsunobu; TOGO, Nozomi; SUNOSE, Yutaka; TAKEYOSHI, Izumi; MAKITA, Fujio (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
A 78-year-old male visited another hospital because of bilateral leg edema. He was found to have a giant abdominal tumor on ultrasonography and was referred to our institution. Abdominal CT and MRI showed an 11-cm low-density tumor on the right and a 37-cm cystic tumor on the left. He was diagnosed with retroperitoneal tumors. We decided to resect the giant left-sided tumor first. One month later, we resected the right-sided tumor. Since the right-sided tumor had invaded the inferior vena cava (IVC), we removed part of the tumor. The resected left-sided tumor weighed 4,780 g and was comprised of yellow, soft, fat-like tissue with a fibrous capsule. The right-sided tumor weighed 291 g and was white and firm. The pathological diagnosis was well-differentiated retroperitoneal liposarcoma. We performed radiation therapy for the remnant tumor around the IVC. The remnant tumor had not progressed 1 year postoperatively, when the patient died of another disease.